PENGARUH INTENSITAS MORAL, KOMITMEN PROFESIONAL, KOMITMEN ORGANISASI, DAN SENSITIVITAS ETIS TERHADAP WHISTLEBLOWING (Studi Kasus Pada Perusahaan Unilever Di Kota Payakumbuh, Bukittinggi, dan Padang) - Xenia Amelia; Yuneita Anisma; Rheny Afriani Anif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted on employees of Unilever company in Payakumbuh, Bukittinggi, and Padang. The samples in this study are all employees related to finance. This research is included in quantitative research. The type of data used in this study is primary data is data derived from the next source in data collection techniques, sampling is done by the method of purposive sampling is the technique of sampling with certain considerations. these data were analyzed using multiple regression with SPSS Version 20. This study aims to determine the effect of Moral Intensity, Professional Commitment, Organizational Commitment, and Ethical Sensitivity to Internal Whistleblowing. The main issues that will be explained by the researcher are as follows: To see how big influence and signifikan between dependent variable with independent variable. The results of this study indicate that Moral Intensity affects Internal Whistleblowing, Professional Commitment affects Internal Whistleblowing, Organizational Commitment affects Internal Whistleblowing, and ethical sensitivity affects Internal Whistleblowing. So the conclusion of this research is all hypothesis presented acceptable.Keywords : Internal Whistleblowing, Moral Intensity, Professional Commitment, Organizational Commitment, Ethical Sensivity.